Skills for the labor market in the Philippines - Di Gropello, Emanuela; Tan, Hong W.; Tandon, Prateek (Directions in Development - General, 2010)
This book investigates trends in skills demand and supply over the past two decades for insights into ways to build (and use) the critical skills needed to sustain competitiveness of the Philippine economy. Part one of the book investigates trends in demand for skills in the country overall and by sectors, explores its possible determinants, and attempts to identify emerging skills gaps. Part two turns to the analysis of the supply of skills in the country with a focus on the ability of education and training to provide highly skilled labor, keeping workers' skills updated, and providing skills development opportunities for the unskilled. It explores employers' perceptions on the quality of institutions and provides detailed analysis of the main characteristics, outcomes, and challenges in four key (or growing) subsectors of the provision of skills in the country: higher education, postsecondary technical-vocational education, non-formal secondary education, and postemployment training. It concludes with a summary of policy recommendations.